Humanized mice in cutaneous leishmaniasis—Suitability analysis of human PBMC transfer into immunodeficient mice. Issue 9 (1st August 2019) - Fischer, Michael R.; Schermann, Anja I.; Twelkmeyer, Trix; Lorenz, Beate; Wegner, Joanna; Jonuleit, Helmut; von Stebut, Esther
Abstract: Humanized mice represent a suitable preclinical test system for example therapeutic interventions in various disease settings, including infections. Here, we intended to establish such system for cutaneous leishmaniasis by infecting T, B and NK cell‐deficient mice adoptively transferred with human peripheral blood mononuclear cells (PBMC). L major infection led to the establishment of parasite lesions harbouring viable parasites and human T cells, but parasite elimination was not seen due to a species‐specific activity of T cell‐derived human IFNγ. In addition, up to 50% of infected mice succumbed to severe graft‐versus‐host disease. In summary, even though long‐term disease outcome assessments are impossible, this model of humanized mice can be used for studying lesion development and generation of oligoclonal anti‐parasite human T cell responses in vivo.